A Comparison of the Quality of Life of Arab Mothers of Children with and without Chronic Disabilities. (2nd July 2016) - Manee, Fahad; Ateya, Yasmeen; Rassafiani, Mehdi
ABSTRACT: Aim . To compare the quality of life (QoL) of Arab mothers in Kuwait who had children with chronic disabilities and those whose children had no disabilities and provide recommendations for how occupational therapists can assist in enhancing the mothers' QOL. Methods . The case group included 71 mothers of children with chronic disabilities and a control group of 86 mothers of children without disabilities. Mothers' QoL was assessed using the Arabic WHOQOL-BREF questionnaire and the support systems of mothers of children with disabilities using a support questionnaire. Results . The QoL of mothers of children with disabilities was significantly lower than that of mothers of healthy children ( p < .001) in all four domains of WHOQOL-BREF (physical health, psychological wellbeing, social relationships, and environment). Mothers of children with disabilities reported that they received most support from their nuclear family. There was a lack of formal support systems in place in Kuwait. Conclusion . Mothers of children with disabilities perceive their QoL as poor and they have limited support systems. Occupational therapists are encouraged to serve as a resource for families, sharing information including available services and community resources, and supporting mothers as competent caregivers.